DOI: 10.35537/10915/4291
|View full text |Cite
|
Sign up to set email alerts
|

Nematodes oxyuridae, trichuridae y capillariidae en roedores akodontini (Cricetidae: sigmodontinae) de la cuenca del Plata, Argentina: su importancia en la interpretación de las relaciones parásito-hospedador-ambiente

Abstract: El objetivo de este trabajo fue estudiar a los nematodes Oxyuridae, Trichuridae y Capillariidae en roedores Akodontini de la Cuenca del Plata (Argentina), enfatizando sobre su grado de especificidad hospedatoria y distribución geográfica. A partir de estos resultados, se interpretaron las relaciones que tienen lugar entre parásitos, hospedador y ambiente. Se consideraron 41 localidades, correspondientes a 7 provincias y 7 eco-regiones, comprendidas en la Cuenca del Plata argentina, en dónde se capturaron roedo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 87 publications
(160 reference statements)
0
4
0
Order By: Relevance
“…Many species of this family are zoonotic, mostly with low specificity at host level but high specificity regarding their location in the host (Anderson, 2000;Moravec, 2001). In America, 16 species of Capillaridae are known as parasites of 10 families of mammals, 4 of them are parasites of rodents of the families Cricetidae, Muridae, Cavidae and Sciuridae (Robles, 2008). Capillariidae exhibit both direct and indirect cycles, with a vertebrate being the definitive host.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many species of this family are zoonotic, mostly with low specificity at host level but high specificity regarding their location in the host (Anderson, 2000;Moravec, 2001). In America, 16 species of Capillaridae are known as parasites of 10 families of mammals, 4 of them are parasites of rodents of the families Cricetidae, Muridae, Cavidae and Sciuridae (Robles, 2008). Capillariidae exhibit both direct and indirect cycles, with a vertebrate being the definitive host.…”
Section: Resultsmentioning
confidence: 99%
“…The genus Echinocoleus is currently distributed in America, Asia and Oceania and comprises 6 species parasitizing the intestine of birds and mammals (Moravec, 2001). The first communication of this genus was from one cricetid rodent from Buenos Aires province (Robles, 2008). The first paleoparasitological record of Echinocoleus was in rodent coprolites collected from the archaeological site Alero Destacamento Guardaparque, located in the Perito Moreno National Park, Santa Cruz Province, dated at 3440 ± 70 years B.P.…”
Section: Resultsmentioning
confidence: 99%
“…In these studies, the comparisons were performed at suprageneric level. Recently, other studies have shown that each Syphacia species appears to be specific to a host genus (Robles, 2008(Robles, , 2010. In the present study, the species 12) Detail of vulva, ventral view (paratype).…”
Section: Discussionmentioning
confidence: 99%
“…Structures such as the shape of the cephalic plate, details and distribution of the submedian papillae and amphids, development of a porous badge, and shape and structure of the accessory hook of the gubernaculum are poorly visualized with light microscopy, but become clear with the SEM Wright, 1973a,b, 1974;Dick et al, 1973;Ogden, 1971;Wiger et al, 1978). To date, all known Syphacia species from Argentina have been studied with SEM and, in future studies, it will be interesting to compare these features with those of different species from around the world Navone, 2007a,b, 2010;Robles et al, 2008;Rojas et al, 2011).…”
Section: Discussionmentioning
confidence: 99%